Deposition and photo-induced electrical resistivity of dip-coated NiO thin films from a precipitation process - Da Silva, Marcelo R. [UNESP]; Scalvi, Luis Vicente de Andrade [UNESP]; Dall'Antonia, Luiz H.; Dos Santos, Dayse I. [UNESP] (Springer Nature, 2013)
Thin films of the semiconductor NiO are deposited using a straightforward combination of simple and versatile techniques: the co-precipitation in aqueous media along with the dip- coating process. The obtained material is characterized by gravimetric/differential thermal analysis (TG-DTA) and X-ray diffraction technique. TG curve shows 30 % of total mass loss, whereas DTA indicates the formation of the NiO phase about 578 K (305 C). X-ray diffraction (XRD) data confirms the FCC crystalline phase of NiO, whose crystallinity increases with thermal annealing temperature. UV-Vis optical absorption measurements are carried out for films deposited on quartz substrate in order to avoid the masking of bandgap evaluation by substrate spectra overlapping. The evaluated bandgap is about 3.0 eV. Current-voltage (I-V) curves measured for different temperatures as well as the temperature-dependent resistivity data show typical semiconductor behavior with the resistivity increasing with the decreasing of temperature. The Arrhenius plot reveals a level 233 meV above the conduction band top, which was attributed to Ni2+ vacancy level, responsible for the p-type electrical nature of NiO, even in undoped samples. Light irradiation on the films leads to a remarkable behavior, because above bandgap light induced a resistivity increase, despite the electron-hole generation. This performance was associated with excitation of the Ni 2+ vacancy level, due to the proximity between energy levels. © 2012 Springer Science+Business Media New York.
Keywords: Current voltage curve; Electrical resistivity; Electron-hole generation; Precipitation process; Semiconductor behavior; Temperature-dependent resistivity; UV-vis optical absorption; X-ray diffraction techniques; Arrhenius plots; Deposits; Electric conductivity; Energy gap; Nickel; Precipitation (chemical); Quartz; Thermoanalysis; Thin films; X ray diffraction; Vapor deposition